Numerical assessment of cold and hot-water floods for a heavy-oil sandstone reservoir in middle east - Alajmi,H; King,PR (16th European Symposium on Improved Oil Recovery 2011, 2011)
A combination of growing energy demand and oil price has been stimulating interests in heavy oil (HO) resources and the methods of exploiting them. Hence, the primary objective of this study is to establish feasible development concepts, among proven technologies, for a heavy oil reservoir in the Middle East. Other objectives include understanding the physics of "selected" EOR methods, and developing a robust screening tool for sandstone HO resources. To accelerate decision-making, a relatively simple screening procedure has been developed and implemented. With this tool, less favourable options have been eliminated, keeping only the 'best' options for further evaluation. For preliminary numerical simulations, a homogenous, three-phase and multi-component numerical model was constructed using known (average) geological, petrophysical and fluid properties of the targeted sector of Reservoir 'X'. Several simulation runs were conducted, investigating the effects of petrophysical properties and operating variables on performances of cold and hot-water flood processes. Simulation results show that the positive impacts of thermal injection on oil production are not instantaneous - they only become noticeable after appreciable number of pore volumes injected. In addition to yielding higher ultimate recovery, the preliminary results also indicate that high-temperature operation accelerates performance.